1997
DOI: 10.1016/s0896-6273(00)81243-x
|View full text |Cite
|
Sign up to set email alerts
|

KIFC2 Is a Novel Neuron-Specific C-Terminal Type Kinesin Superfamily Motor for Dendritic Transport of Multivesicular Body-Like Organelles

Abstract: We have cloned two novel C-terminal motor domain-type kinesin superfamily motor proteins (KIFCs) from mouse brain by utilizing a KIFC-specific consensus sequence. The first protein was the murine homologue of CHO2 antigen, a member of the kar3-type mitotic motor subfamily, and we designated this protein KIFC1. The other protein, KIFC2 (792 amino acids), is novel, with no significant similarity to known kinesin superfamily proteins (KIFs). KIFC2 was specifically expressed in adult neurons, and was immunofluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
132
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(140 citation statements)
references
References 63 publications
8
132
0
Order By: Relevance
“…Previously, we have identified 25 KIFs in mice (11,(18)(19)(20)(21)(22). Most were found by using molecular biological approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have identified 25 KIFs in mice (11,(18)(19)(20)(21)(22). Most were found by using molecular biological approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Thus minusend-directed motility of early endocytic vesicles is mediated by Kifc2 in the rat and Kifc1 in the mouse. These are genetically distinct proteins with little homology (Saito et al, 1997). Specific regions of a number of kinesins that interact with and bind to cargo have been identified previously (Hirokawa, 1998;Verhey et al, 2001;Smith et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Using these tools, we found that plus-end motility of early endocytic vesicles from rat liver was mediated by the conventional kinesin Kif5B (standardized nomenclature kinesin-1) (Miki et al, 2003(Miki et al, , 2005Lawrence et al, 2004), and minus-end motility was mediated by Kifc2 (standardized nomenclature kinesin-14B) (Bananis et al, , 2003(Bananis et al, , 2004Murray et al, 2000). Whereas Kifc2 was initially described as a brain-specific minus-enddirected kinesin Saito et al, 1997), our studies showed that it was highly associated with these vesicles prepared from rat liver (Bananis et al, 2003). Although the rat is a convenient experimental animal, the power of genetic models that have been established in the mouse led us, in the present study, to examine microtubulebased motility and processing of early endocytic vesicles derived from mouse liver.…”
mentioning
confidence: 99%
“…They include Rab8 (Huber et al, 1993a,b), KIFC2 (Saito et al, 1997), KIF17 (Setou et al, 2000;Guillaud et al, 2003), AP-1 (Eiraku et al, 2002), and AP-4 (Yap et al, 2003). At present, it remains unknown what molecule interacts with the cytoplasmic tail of TLCN.…”
Section: A Transgenic Mouse System For Analysis Of Polarized Targetinmentioning
confidence: 99%